1997
DOI: 10.1074/jbc.272.10.6245
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Impairment in Niemann-Pick Type C Disease

Abstract: Niemann-Pick type C disease (NPC) belongs to the group of lysosomal storage diseases characterized by an accumulation of cholesterol and sphingomyelin. Using a mutant mouse strain, enzymatic markers for lysosomes, mitochondria, microsomes, and peroxisomes were investigated in the liver and brain. Aside from lysosomal changes, we found a sizable decrease of peroxisomal ␤-oxidation of fatty acids and catalase activity in the brain and liver. Isolated peroxisomes displayed a significant decrease of these enzyme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 38 publications
0
51
1
Order By: Relevance
“…Although NPC belongs to the group of lysosomal storage diseases characterized by an accumulation of cholesterol and sphingomyelin in lysosomes, studies of BALB/cNctr-Npc1 m1N /J mice, a spontaneous mutant mouse model of Npc1 deficiency, suggest additional effects on peroxisome function. A sizeable decrease of peroxisomal ␤-oxidation of fatty acids and catalase activity was observed in mouse NPC 18 days before the onset of signs of disease, while lysosomal enzymatic function did not decline until 6 days afterward (44). BALB/cNctr-Npc1 m1N /J mice also express CD1d at lower levels in their thymi than do wild-type mice, and they lack type 1 NKT cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although NPC belongs to the group of lysosomal storage diseases characterized by an accumulation of cholesterol and sphingomyelin in lysosomes, studies of BALB/cNctr-Npc1 m1N /J mice, a spontaneous mutant mouse model of Npc1 deficiency, suggest additional effects on peroxisome function. A sizeable decrease of peroxisomal ␤-oxidation of fatty acids and catalase activity was observed in mouse NPC 18 days before the onset of signs of disease, while lysosomal enzymatic function did not decline until 6 days afterward (44). BALB/cNctr-Npc1 m1N /J mice also express CD1d at lower levels in their thymi than do wild-type mice, and they lack type 1 NKT cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Second was a report that plasmalogen levels were reduced in brain tissue from the NPC mouse model (12), which likely results from the impaired peroxisomal function found in NPC brain. The NPC1 gene defect results in reduced transport of cholesterol, glycosphingolipids, and fluid phase constituents out of lysosomes and late endosomes (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of plasmalogens did not alter the rate of cellular cholesterol transfer to HDL; instead, it appeared to reduce the pool of cholesterol available for efflux. Another study showed that levels of PlsEtn are reduced in brain tissue from the Niemann-Pick C (NPC) mouse model (12). NPC cells exhibit lysosomal storage of cholesterol, gangliosides, and other lipids, as well as aberrant cholesterol homeostatic responses (13).…”
mentioning
confidence: 99%
“…Cell fusion studies using primary cultures of patients' skin fi broblasts and a cell line derived from the spontaneously occurring mouse model of NPC identifi ed NPC1 and NPC2 as genetic complementation groups ( 102 ). Biochemical studies of this mouse identifi ed early peroxisomal impairment (by 18 days) in the development of its disease ( 103 ). The responsible locus in the mouse was localized to chromosome 18 ( 104 ), and linkage was then established in the syntenic region of human chromosome 18q11-q12 ( 105 ).…”
Section: Cholesterol Efflux From Endosomes: Npc Proteins and Niemann-mentioning
confidence: 99%